(untitled) (Journal of Geography and Environmental Management, 2016)
In this work has been considered climatic features of a thermal mode during the summer period in the South Kazakhstan area. Statistical characteristics of temperature of air have been calculated. Extremely cold and extremely warm months during the summer period have been defi ned.